Analisis Semantik: Nilai Persahabatan antara Piko dan Ucup melalui Dialog Film Mencuri Raden Saleh - Reza Pahlevi Ginting; Abdul Azis (Jurnal Ilmiah Kanderang Tingang, 2023)
Mencuri Raden Saleh is a film that tells the story of the lives of young people. It starts with Piko (Iqbaal Ramadhan), an art student who is struggling to find money to support himself and trying to free his father who is in prison. Researchers use semantic meaning which is a part of linguistics that examines meaning or significance (Parera, 2004). The value of friendship is mutual understanding between individuals, understanding all things that are liked, hated, needed, as well as the elements that make up a feeling that requires each individual to trust each other, help each other, and work together to develop common goals (Pangle in Julia, 2021). Researchers used qualitative methods in analyzing data and descriptive methods in presenting research data. The technique used in data collection is the Talk Free Involvement Listening Technique (Zaim, 2014). Based on the results of data analysis, it can be concluded, namely 1) dominant semantic meaning can be carried out, namely emotive and ideational meanings, 2) friendship values ​​that arise, namely mutual support, mutual trust, and responsibility for the difficulties experienced by the two friends , and 3) this research can also be a reference in understanding the value of friendship for students and used as research material that can be developed in social life.